What is the Effect of U.S. Antidumping Duties on Imports? Some Evidence from the Sunset Review Process - William W. Nye (U.S. Department of Justice, Antitrust Division, Economic Analysis Group (EAG), 2006)
The voluminous literature on the U.S. antidumping laws has a curious lacuna. There is little in this literature about the effects of antidumping duties on the volume of subject imports. One reason this key question has not frequently been investigated is the lack of data. U.S. antidumping duties are firm specific, while information about U.S. imports is collected by commodity and country, but not by firm. This paper avoids this problem by examining a sample of U.S. antidumping orders for which the duties were the same for all firms from a given country, or for which there was only one foreign firm exporting the product from the foreign country in question. Using this sample, the present paper is the first study of which the author is aware that investigates the relation between antidumping duties and subject imports using accurate information about the level of antidumping duties. The paper is also unique in accurately measuring the quantity of imports affected by the antidumping duties. The study uses import quantity data reported by the USITC in its Sunset Review reports, rather than using ten-digit HTUSA categories, which sometimes do not match antidumping product definitions precisely. The price of using this unique dataset is that the current study is restricted to a sample of only 32 of the approximately 350 antidumping orders originating during the relevant years, of which about 188 are still in effect. Some evidence is presented suggesting that the sample of orders used may be representative of the larger universe. For the sample examined, the paper finds an elasticity of subject imports with respect to U.S. antidumping duties of roughly 0.9. The paper also finds some evidence that age of the antidumping order may be a factor in explaining reduction in volume of subject imports. Study of this effect may be complicated by the fact that the initial level of all U.S. antidumping duties was lower during the early 1980s than in the early 1990s; so older orders tend to have lower duties. The study finds inconclusive evidence about the effect of antidumping orders on the price received by the foreign suppliers of subject imports.
Keywords: 330